Transformation of the myth into the tales (Eurasian Journal of Philology Science and Education, 2020)
One can see mythology at the beginning of culture and thought. Folklore, including fairy tales, is a continuation or reproduction of mythology. Myths have given the great incitements not only to folklore genres, but also to the development of literature. As folklore is derived from myths and literature is derived from folklore, later myths were re-applied in the history of literature. The tales about animals and magical images are more connected with myths among the tales. Animals are the oldest and main characters of myths. The transition of myths to other folklore genres, including fairy tales, has taken place in the form of a long-term process. While the myths were transformed into folklore, there was also the layering of myths and tales. As magical tales or the tales about the animals are directly derived from myths, tales that live along with myths have come together in common motives. When myths are transformed into the tales, as well as other folklore genres, they lose their function and become literaryaesthetic texts. Both myths and fairy tales that are about the same mythical characters differ from each other in this point. While a mythical image is perceived as a real being that same image in the tale is already perceived as a fictitious, unrealistic image.